2020
DOI: 10.20525/ijrbs.v9i5.830
|View full text |Cite
|
Sign up to set email alerts
|

The practice of job crafting and its impact on job outcomes

Abstract: This study aims to investigate the effect of job crafting practices on job outcomes (work engagement and job satisfaction). This research was conducted on workers at Perseroan Terbatas (PT). Petra Arun Gas (PAG) with a working population of 180 people. Samples were taken as many as 123 people based on Krejcie and Morgan Sample Tables (in Sekaran & Bougie, 2009, pp. 254-255). The selection of sample members was carried out using the simple random sampling method. Primary data is obtained by distributing que… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
3
0
1

Year Published

2022
2022
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 34 publications
0
3
0
1
Order By: Relevance
“…This would result in a negative feed-back in terms of performance that could impact affective commitment [139]. Because job satisfaction is also a feeling of success of workers in work [140], and in previous research [141] job satisfaction has been identified as a protective factor between stressors factors and affective commitment, the presence of good job satisfaction can act as a mediator and strengthen the link between job crafting and affective commitment.…”
Section: Job Satisfaction As a Mediator Between Job Crafting And Affe...mentioning
confidence: 95%
“…This would result in a negative feed-back in terms of performance that could impact affective commitment [139]. Because job satisfaction is also a feeling of success of workers in work [140], and in previous research [141] job satisfaction has been identified as a protective factor between stressors factors and affective commitment, the presence of good job satisfaction can act as a mediator and strengthen the link between job crafting and affective commitment.…”
Section: Job Satisfaction As a Mediator Between Job Crafting And Affe...mentioning
confidence: 95%
“…Kaynakları Koruma Teorisi (Hobfoll, 1989) bağlamında, iş kaynaklarına sahip olan ve bunları koruyan bireyler; iş talepleriyle kolaylıkla başa çıkmakta, kişisel öğrenmeyi gerçekleştirmekte, iş hedeflerine ulaşmakta, daha az stres yaşamakta ve işlerini biçimlendirmektedirler (Schaufeli & Bakker, 2004;Bakker, Veldhoven & Xanthopoulou, 2010). İşlerini biçimlendiren bireylerin iş performansları artmakta, tükenmişlik düzeyleri azalmakta, iş tatmin ve işe tutulma düzeyleri yükselmektedir (Nguyen, Nguyen, Ngo & Nguyen, 2019;Karollah, Monita, Vilzati, Muhammad & Ibrahim, 2020). Bu anlayışla, iş kaynakları ile işe tutulma arasındaki ilişkide iş biçimlendirmenin aracılık rolü üstlendiği ifade edilebilir (Basım, Güler & Ocak, 2021).…”
Section: İş Biçimlendirme Ve İşe Tutulma İlişkisiunclassified
“…In order to perceive the environment of working, it is crucial to make sure that, employee is working in an enjoyable environment. Such environment could be very significant and fruitful for majority of employees if the management support them by giving them the chance to enhance and express their abilities and personalities (Jordan et al, 2017;Karollah et al, 2020). Consequently, such support gives them the opportunity to be creative in improving current working designs or developing new designs in order to help them in expressing their feelings and achieve what they want to do in a proper way.…”
Section: Introductionmentioning
confidence: 99%
“…Actually, there is a significant relationship between employees' job crafting and service recovery performance which indicates the positive impact of personalizing working environment (Hetland et al, 2018;Cheng and O-Yang, 2018). However, the role of management in any hospitality enterprize is to express themselves as such process flows from the subordinate level to the managerial one clearly (Thomas et al 2020;Karollah et al 2020;Brucker and Sundar, 2020).…”
Section: Introductionmentioning
confidence: 99%